Governing the liberated child with self-managed family displays. (November 2014) - Haldar, Marit; Engebretsen, Eivind
The 1990s witnessed the replacement of psychological perspectives seeing children as 'becomings' to a view of them as 'beings'. This is challenged by the Foucauldian concept of governmentality understood as technologies of self-making actors capable of monitoring and controlling their own behaviour. This concept is central in the present study of so-called teddy-diaries, which are texts written by first graders and their parents and circulated among other families as part of the Norwegian school curriculum. A key finding of the analyses is that these circulated and displayed texts represent technologies for governing families – especially in reinforcing expectations about how 'normal' childhood and family life should be lived.